Tryptamine Synthesis by Iron Porphyrin Catalyzed C−H Functionalization of Indoles with Diazoacetonitrile. Issue 11 (4th February 2019) - Hock, Katharina J.; Knorrscheidt, Anja; Hommelsheim, Renè; Ho, Junming; Weissenborn, Martin J.; Koenigs, Rene M.
Abstract: The functionalization of C−H bonds with non‐precious metal catalysts is an important research area for the development of efficient and sustainable processes. Herein, we describe the development of iron porphyrin catalyzed reactions of diazoacetonitrile with N‐heterocycles yielding important precursors of tryptamines, along with experimental mechanistic studies and proof‐of‐concept studies of an enzymatic process with YfeX enzyme. By using readily available FeTPPCl, we achieved the highly efficient C−H functionalization of indole and indazole heterocycles. These transformations feature mild reaction conditions, excellent yields with broad functional group tolerance, can be conducted on gram scale, and thus provide a unique streamlined access to tryptamines. Abstract : An iron porphyrin catalyst furnishes acetonitrile‐functionalized indole derivatives by C−H functionalization reactions of protected and unprotected indole heterocycles with diazoacetonitrile. This process streamlines the synthesis of valuable tryptamines for applications in total synthesis and drug discovery.